INDONESIAN-ENGLISH CODE-MIXING IN INSTAGRAM CAPTIONS OF AN INDONESIAN CELEBGRAM - Dewi, Gusti Putu Rustika; Adnyani, Ni Luh Putu Sri; Padmadewi, Ni Nyoman; Suwastini, Ni Komang Arie; Jayantini, I Gusti Agung Sri Rwa (Universitas PGRI Sumatera Barat, 2021)
Code mixing is a sociolinguistic phenomenon that deals with bilingual speakers' ability to use language features of two languages in one sentence or utterance. This research investigated the type of code-mixing used by an Indonesian celebgram and explored reasons for using code-mixing in Instagram captions of an Indonesian celebgram. The data for this study were collected from Instagram captions posted by an Indonesian celebgram @keanuagl from February 2020 to September 2020. The data were analyzed by using Muysken’s theory of type of code-mixing. The reasons for using code-mixing in Instagram captions were analyzed using Hoffman's theory which covers seven reasons. The findings showed that insertion was the most frequent type of code-mixing used by @keanuagl. It was followed by congruent lexicalization, and the minor type used was alternation. It was found that the percentage of insertion was 68.96%, alternation was 10.34%, and congruent lexicalization was 20.68%. For the reason of using code-mixing, it was found that there were only three reasons that motivated the use of code-mixing by @keanuagl in his Instagram captions. Those reasons were to talk about a particular topic, show empathy or solidarity, and intend to clarify the speech content for the interlocutor.